Anticerebral Ischemia-Reperfusion Injury Activity of Synthesized Puerarin Derivatives. (11th October 2016) - Ji, Yubin; Jiang, Pei; Yan, Xinjia
Abstract : When cerebral ischemia-reperfusion injury happened in patients, multiple pathological processes occur, such as leukocyte infiltration, platelet, and complement activation, which would result in cognitive dysfunction and inflammation. Puerarin has shown protective effect on injury of neural cell. In order to enhance this protective effect of puerarin, puerarin derivatives with different log ⁡ P values were designed and synthesized. The original phenolic hydroxyl in the puerarin molecules was substituted in order to change the blood-brain barrier permeability and thus enhance the efficacy for preventing cerebral ischemia/reperfusion injury. And the structure of the newly synthesized molecules was confirmed by 1H NMR spectroscopy and mass spectrometry. The mouse model of cerebral artery ischemia/reperfusion injury was established to test the anticerebral ischemia-reperfusion injury activity of the puerarin derivatives. The assays of the water maze, Y maze, brain cortex Ca 2+ -Mg 2+ -ATP enzyme, and iNOS enzyme activity were performed in this mouse model. The results showed that puerarin derivative P1-EA and P2-EA were resulting in an increased lipophilicity that enabled the derivatives to pass more efficiently through the blood-brain barrier, thus, improving the protective effects against cerebral ischemia/reperfusion injury. Therefore, derivatives of puerarin may serve as promising approach to improve neuron function in ischemia-reperfusion brain injury-related disorders.